Mobility in Transition Migration Patterns after EU Enlargement - Grabowska-Lusinska, Izabela; Kuvik, Aimee; Glorius, Birgit (IMISCOE Research, 2013)
This volume presents new research on post-accession migration from Central and Eastern Europe in the short period since the EU enlargements of 2004 and 2007. Explanations of post-accession migration patterns, trends and mechanisms delve into the complexities of these phenomena. New groups of migrants and types of migrations are identified -- such as young migrants, often students or graduates, without family obligations and without clear plans concerning their future life. Case studies on Poland, Romania, Hungary and Latvia as well as the United Kingdom and Germany - being major destination countries - divulge the multifaceted nature of transition, whether in the form of labour migration, short-term mobility (including among international students) or return migration. The volume insightfully points towards future migration trends and sets guidelines for further research.